Permineralized osmundaceous and gleicheniaceous ferns from the Jurassic of Inner Mongolia, NE China - Tian, Ning; Wang, Yong-Dong; Zhang, Wu; Zheng, Shao-Lin; Zhu, Zhi-Peng; Liu, Zhong-Jian (Palaeobiodiversity and Palaeoenvironments, 2018)
Structurally preserved fossil ferns are extremely significant for exploring the origin and evolution of this plant clade; however, they are quite scarce and limited in the Mesozoic. Here, we report some well-preserved fern rhizomes and rachides with anatomical details from the Upper Jurassic Manketouebo Formation in Inner Mongolia, NE China. Two taxa, including Ashicaulis liaoningensis (Zhang et Zheng) Tidwell referred to Osmundaceae and Gleicheniorachis sinensis sp. nov. referred to Gleicheniaceae, are recognized. Anatomically, Ashicaulis liaoningensis consists of a heterogeneous pith, an ectophloic dictyoxylic siphonostele, a two-layered cortex, C-shaped leaf traces, and a mantle of petiole bases. The petiole base is characterized by a heterogeneous sclerotic ring with an abaxial thick-walled fiber arc. Gleicheniorachis sinensis sp. nov. consists of a C-shaped vascular bundle with two incurved adaxial hooks, a distinct sclerenchyma sheath, an endodermis, and a heterogeneous cortex. In particular, the finding of Gleicheniorachis sinensis sp. nov. represents the first report of unequivocal Jurassic record of Gleicheniaceae in northern China, as well as the first record of a Jurassic permineralized gleicheniaceous fern in the Northern Hemisphere. This study provides new data and evidence for exploring the anatomical diversity and evolution of Mesozoic ferns, and contributes to further understanding the floral composition of Late Jurassic flora in Northeast China.